Recent advances in Hodge theory period domains, algebraic cycles, and arithmetic - Kerr, Matt 1975-; Pearlstein, Gregory 1970- (Cambridge University Press, 2016)
Papers from the summer school and conference: Recent advances in Hodge theory : period domains, algebraic cycles, and arithmetic; held from June 10-20, 2013, at the Pacific Institute of Mathematical Sciences, University of British Columbia, Vancouver, Canada
Keywords: Algebraic cycles -- Congresses; Hodge theory -- Congresses; Geometry, Algebraic -- Congresses; Differential-algebraic equations -- Congresses; Hodge-Theorie; Konferenzschrift